Isoprene Emission in Darkness by a Facultative Heterotrophic Green Alga - Dani, K. G. Srikanta; Torzillo, Giuseppe; Michelozzi, Marco; Baraldi, Rita; Loreto, Francesco (Frontiers in Plant Science, 2020)
Isoprene is a highly reactive biogenic volatile hydrocarbon that strongly influences atmospheric oxidation chemistry and secondary organic aerosol budget. Many phytoplankton emit isoprene like terrestrial pants. Planktonic isoprene emission is stimulated by light and heat, and is seemingly dependent on photosynthesis, as in higher plants. However, prominent isoprene-emitting phytoplankton are known to survive also as mixotrophs and heterotrophs. Chlorella vulgaris strain G-120, a unicellular green alga capable of both photoautotrophic and heterotrophic growth, was examined for isoprene emission using GC-MS and real time PTR-MS in light (+CO2) and in darkness (+glucose). Chlorella emitted isoprene at the same rate both as a photoautotroph under light, and as an exclusive heterotroph while feeding on exogenous glucose in complete darkness. By implication, isoprene synthesis in eukaryotic phytoplankton can be fully supported by glycolytic pathways in absence of photosynthesis, which is not the case in higher plants. Isoprene emission by chlorophyll-depleted mixotrophs and heterotrophs in darkness serves unknown functions and may contribute to anomalies in oceanic isoprene estimates.